Dampak User Generated Content (UGC) dan Brand Equity terhadap Brand Trust: Studi Kasus pada Produk Kosmetik Lokal - Linah Destianah; Nina Nurhasanah (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid growth of the digital era has driven businesses to utilize social media as an effective and efficient marketing tool. One influential form of content in digital marketing is User-Generated Content (UGC), which has been proven to shape consumer perception and trust toward a brand. This study aims to examine the influence of UGC and Brand Equity on Brand Trust in the case of a local cosmetic brand, Instaperfect. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The population in this study consisted of women residing in West Jakarta who had purchased Instaperfect products after seeing them on social media. The sampling technique used was purposive sampling with a total of 105 respondents. The results revealed that UGC has a significant positive effect on both Brand Equity and Brand Trust, while Brand Equity does not have a significant effect on Brand Trust. These findings suggest that consumer trust is more influenced by authentic user experiences shared through UGC rather than brand image alone. This study contributes to the business sector by offering strategic insights on leveraging usergenerated content to enhance Brand Trust and consumer loyalty in the digital age.